2015
DOI: 10.3390/su7043615
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Delivering Green Building Projects: Unearthing the Transaction Costs (TCs)

Abstract: Delivering green building (GB) projects involve some activities that are atypical in comparison with conventional buildings. Such new activities are characterized by uncertainty, and they incur hidden costs that have not been expected nor are they readily appreciated among the stakeholders. This paper develops a typology and chronology to examine the new activities that are associated with transaction costs (TCs) in the real estate development process (REDP) of green building. Through in-depth interviews with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…For example, sustainable construction can appear more expensive when construction professionals are unaware of these possible risks and, as a result, assign higher contingencies [15]. The opposite can also be true.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, sustainable construction can appear more expensive when construction professionals are unaware of these possible risks and, as a result, assign higher contingencies [15]. The opposite can also be true.…”
Section: Introductionmentioning
confidence: 82%
“…Unavailability of sustainable building materials [63] Handling recycled materials puts construction workers at safety risks [43] Poor material quality [26] Unavailability of specific equipment [15] Uncertainty in the performance of sustainable materials [59] Additional responsibilities for construction maintenance [59] Non-complying products and materials [26] Lack of practical experience [15] Change in material types and specifications during construction [43] Uncertainty with specialized sustainable equipment [51] …”
Section: Labor and Equipmentmentioning
confidence: 99%
“…Research on the barriers to the implementation of SC practices has gained worldwide attention [37,55,65,68]; however, there is a dearth of studies on the subject from developing countries in the relevant literature [69]. Therefore, this study has identified and ranked the barriers to SC according to their importance level as perceived by industry professionals in Cambodia.…”
Section: Barriers To Sustainable Constructionmentioning
confidence: 99%
“…Is it due to their highly complex nature which may lead to transaction costs that are either too high or too risky to predict (Sorrell, 2007)? We suggest that umbrella agreements may help to reduce and manage these transaction costs and therefore to increase the feasibility of previously difficult or unviable sustainability goals (Qian and Guo, 2014, Qian et al, 2012, Qian et al, 2015. Other potentially exciting areas of empirical research could include advanced waste reduction and recycling schemes; efficient supply chain, distribution and reverse logistics; and industry-wide efforts such as sustainable fishing, logging, or water sourcing.…”
Section: Recursive Time -Managing Repeated Review Cycles • Manifold Rmentioning
confidence: 99%